2014
DOI: 10.1186/1475-2859-13-7
|View full text |Cite
|
Sign up to set email alerts
|

Modified ‘one amino acid-one codon’ engineering of high GC content TaqII-coding gene from thermophilic Thermus aquaticus results in radical expression increase

Abstract: BackgroundAn industrial approach to protein production demands maximization of cloned gene expression, balanced with the recombinant host’s viability. Expression of toxic genes from thermophiles poses particular difficulties due to high GC content, mRNA secondary structures, rare codon usage and impairing the host’s coding plasmid replication.TaqII belongs to a family of bifunctional enzymes, which are a fusion of the restriction endonuclease (REase) and methyltransferase (MTase) activities in a single polypep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
0
20
0
1
Order By: Relevance
“…To improve the expression levels of the S protein, S gene sequences were codon optimized with the strategy of 'one amino acid-one codon', in which the most preferred codon of the host for a given amino acid is used in the target sequence without changing the amino acid sequences [22]. The nucleotide sequences of the CV777 and LNCT2 S genes were edited in accordance with the codon table for Homo sapiens in the Codon Usage Database (http://www.…”
Section: Construction Of Expression Vectorsmentioning
confidence: 99%
“…To improve the expression levels of the S protein, S gene sequences were codon optimized with the strategy of 'one amino acid-one codon', in which the most preferred codon of the host for a given amino acid is used in the target sequence without changing the amino acid sequences [22]. The nucleotide sequences of the CV777 and LNCT2 S genes were edited in accordance with the codon table for Homo sapiens in the Codon Usage Database (http://www.…”
Section: Construction Of Expression Vectorsmentioning
confidence: 99%
“…To determine whether the S protein of PEDV was recognized by mAb 1B9, the S gene, as well as the S1 and S2 genes, of the CV777 and LNCT2 strains were cloned into plasmid pcDNA3.1(-). To improve the expression level of the S protein, the S gene sequences of the CV777 and LNCT2 strains were codon optimized using a 'one amino acid-one codon' strategy, without changing their amino acid sequences (Wang et al, 2016;Zylicz-Stachula et al, 2014). The results showed that mAb 1B9 only reacted with cells that were transfected with pcDNA3.1(-)-CV777-S or pcDNA3.1 (-)-LNCT2-S.…”
Section: Discussionmentioning
confidence: 99%
“…The strategy of codon optimization developed in this study is known as ‘one amino acid-one codon’, in which the most preferred codon of the host for a given amino acid is used in the target sequence [16]. Online optimization software (http://www.jcat.de/ and http://genomes.urv.es/OPTIMIZER/) were utilized for codon design.…”
Section: Methodsmentioning
confidence: 99%